2024
DOI: 10.12998/wjcc.v12.i5.880
|View full text |Cite
|
Sign up to set email alerts
|

Causal associations between gastroesophageal reflux disease and essential hypertension: A bidirectional Mendelian randomization study

Ning Wei,
Ming-Hui Liu,
Yu-Hu Song

Abstract: BACKGROUND Clinical studies have reported that patients with gastroesophageal reflux disease (GERD) have a higher prevalence of hypertension. AIM To performed a bidirectional Mendelian randomization (MR) analysis to investigate the causal link between GERD and essential hypertension. METHODS Eligible single nucleotide polymorphisms (SNPs) were selected, and weighted median, inverse variance weighted (IVW) as well as MR egger (MR-Egger) regression were used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…There are common risk factors for GERD and hypertension, such as obesity, age, male gender, and smoking [ 38 - 40 ]. Suyu et al [ 41 ] found that hypertension is a positive predictor for GERD, especially silent GERD.…”
Section: Discussionmentioning
confidence: 99%
“…There are common risk factors for GERD and hypertension, such as obesity, age, male gender, and smoking [ 38 - 40 ]. Suyu et al [ 41 ] found that hypertension is a positive predictor for GERD, especially silent GERD.…”
Section: Discussionmentioning
confidence: 99%